Pengaruh Perencanaan Pajak, Profitabilitas, Ukuran Perusahaan, dan Kualitas Audit Terhadap Manajemen Laba - Shella Shintia; Jasmina Syafei (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study is included in the type of quantitative research that aims to analyze the effect of tax planning, profitability, company size, and audit quality on earnings management practices in property and real estate companies listed on the Indonesia Stock Exchange during the period 2021–2024. Sampling was carried out using the purposive sampling method, so that 28 companies were obtained as research samples. The data used are secondary data sourced from the company's financial statements. The analysis technique used is panel data regression with the help of EViews 12 software. The results of the study indicate that tax planning does not affect earnings management, company size, profitability and audit quality affect earnings management.